Non-metal-doped bulk carbon material for adsorbing thallium, preparation method and method for removing thallium from water

A non-metal-doped bulk carbon material addresses inefficiencies in thallium removal by providing a simple, cost-effective, and recyclable solution for both low and high thallium concentrations across a wide pH range, achieving superior removal efficiency and compliance with stringent water quality standards.

CN116272872BActive Publication Date: 2024-12-24HUNAN DAQING ECOLOGICAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310467221.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2024-12-24
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

Existing methods for removing thallium from water are inefficient, costly, generate secondary pollution, and have narrow pH application ranges, with adsorbents being complex, difficult to recycle, and ineffective at low or high concentrations.

Method used

A non-metal-doped bulk carbon material derived from biomass or synthetic polymers, doped with N, O, P, or S, is carbonized at high temperatures to create a porous structure for adsorbing thallium, allowing for wide pH range operation and easy recycling.

Benefits of technology

The material effectively removes thallium to below 5 μg/L, meeting industrial standards and 0.1 μg/L drinking water standards, with high efficiency and low cost, and can be reused multiple times without secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272872B_ABST
    Figure CN116272872B_ABST
Patent Text Reader

Abstract

The present invention discloses a non-metallic doped bulk carbon material for adsorbing thallium, a preparation method and a method for removing thallium from water. The non-metallic doped bulk carbon material is obtained by directly carbonizing a bulk precursor rich in non-metallic elements; the non-metallic elements are one or more of N, O, P and S. The non-metallic doped bulk carbon material of the present invention is simple to prepare, non-toxic and pollution-free, easy to separate and operate, and does not require the addition of any additional reagents. Moreover, under the same adsorbent dosage and thallium concentration conditions, the thallium removal effect of the adsorbent of the present invention is better than other disclosed methods. The efficient removal of thallium from water by the adsorbent of the present invention is achieved through multiple effects such as chemical adsorption of lone pairs of electrons of non-metallic atoms in the adsorbent material coordinated with thallium ions and physical adsorption of the porous structure of the adsorbent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a non-metal-doped bulk carbon material for adsorbing thallium, a preparation method and a method for removing thallium from water. Background Art

[0002] Thallium (Tl) is a highly toxic heavy metal. Thallium poisoning can cause hair loss, blindness, multiple neurosis, and even death. Thallium exists in nature in two valence states: monovalent and trivalent, and mainly in the form of monovalent thallium. Due to the high toxicity of thallium, China's industrial emission standards stipulate that the thallium content in industrial discharge water shall not exceed 5μg / L, and some provinces stipulate that it shall not exceed 2μg / L. my country's drinking water hygiene standards stipulate that the thallium content in water shall not exceed 0.1μg / L.

[0003] At present, the methods for removing thallium from water include chemical oxidation-precipitation, ion exchange, solvent extraction, biotechnology, etc. However, these methods generally have disadvantages such as low removal efficiency, large amount of waste residue generated, and high energy consumption. In comparison, adsorption technology has great application potential in the field of water treatment due to its advantages such as low energy consumption and easy operation. At present, the reports on the removal of thallium from water by adsorption are very limited, and the effect is not ideal. The composition and preparation of the adsorbent are complex. The development of efficient adsorbent materials is the key to the green and efficient treatment of thallium-containing water.

[0004] CN114377652A discloses a nano-composite thallium removal agent and a method for treating thallium-containing wastewater. The nano-composite thallium removal agent includes a nano-carrier, Fe3O4 nanoparticles and Prussian blue, and treats thallium wastewater with a pH between 6 and 10. The nano-powder is difficult to separate and cannot be reused. The method requires the initial concentration of thallium-containing wastewater to be no higher than 200 μg / L, and is not suitable for treating wastewater with a higher thallium concentration.

[0005] CN113526606A discloses a thallium removal agent and a preparation method thereof, comprising the following components: activated carbon, urea, sodium diethyldithiocarbamate, activated clay, organic alkane, heavy metal scavenger, linear small molecule amine substances, surfactant and ferrous chloride. The thallium in the water body is removed by organic-inorganic co-flocculation and activated carbon / activated clay adsorption. The concentration of thallium in the residual liquid with the best thallium removal effect is still as high as 0.04 mg / L (40 μg / L), which does not meet the industrial emission standard (no more than 5 μg / L).

[0006] CN113603179A discloses a method for preparing composite biochar and removing thallium-containing wastewater, which mainly involves adding zero-valent manganese-loaded biochar and hypochlorite to thallium-containing wastewater, and the hypochlorite oxidizes monovalent thallium into trivalent thallium, and removes it by adsorption. The preparation of biochar loaded with zero-valent manganese is complicated, involving operations such as calcination, hydrothermal reaction, water washing, centrifugation, and freeze-drying. The adsorbent is required to avoid exposure to air, in which zero-valent manganese is easily oxidized and ineffective. This method is only applicable to the treatment of thallium-containing ammonia nitrogen wastewater, and the removal conditions for thallium require a pH of 10 and the addition of hypochlorite. After the best treatment effect, the concentration of thallium in the water body is still as high as 2.98mmol / L (609mg / L) (the initial concentration of monovalent thallium is 10mmol / L, and the removal rate is 70.2%). The removal effect of low-concentration thallium is not reflected, and the safe discharge of thallium-containing wastewater cannot be guaranteed.

[0007] The above disclosed methods for removing and adsorbing thallium all use metals and their compounds, and the adsorbents are mostly powders, and organic reagents or strong oxidants are also used. The above disclosed methods for removing thallium mainly have the following shortcomings: complex composition, high metal cost and easy to cause secondary pollution; difficult to recycle powder materials and high cost of reuse; organic reagents cannot be reused, increase the cost of use and cause secondary pollution; oxidants cannot be reused, increase the cost of use and cause secondary pollution; the treatment effect of low concentration (such as CN113603179A) or high concentration (such as CN114377652A) thallium-containing wastewater is not good; the pH application range of thallium-containing wastewater is narrow. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a non-metallic doped bulk carbon material for adsorbing thallium, a preparation method and a method for removing thallium from water. The non-metallic doped bulk carbon material has the advantages of simple preparation, low cost, green environmental protection, easy large-scale production and easy recycling.

[0009] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0010] The invention provides a non-metallic doped bulk carbon material for absorbing thallium, which is obtained by directly carbonizing a bulk precursor rich in non-metallic elements; the non-metallic elements are one or more of N, O, P and S.

[0011] Preferably, the non-metal-doped bulk carbon material has a porous structure.

[0012] Preferably, the block precursor rich in non-metallic elements is a biomass material or a synthetic polymer material.

[0013] More preferably, the biomass material is one of soybeans, pumpkin seeds, sunflower seeds, wheat, green onions, onions, buckwheat husks, walnut shells, chestnut shells, etc.

[0014] More preferably, the synthetic polymer material is one of polyvinyl alcohol, polyoxymethylene, polylactic acid, polyacrylic acid, polyacrylic acid derivatives, polythiophene, polyamide, polypyrrole, polyphosphazene, polyurethane, polyether, polyester, polyphenylene sulfide, polyurea and the like.

[0015] Preferably, in the non-metal-doped bulk carbon material for adsorbing thallium, the doping amount of the non-metal is 5% to 35%.

[0016] The present invention also provides a method for preparing the non-metal-doped bulk carbon material for adsorbing thallium, comprising:

[0017] The non-metal-rich bulk precursor is carbonized into a non-metal-doped bulk carbon material using high temperature in an inert gas atmosphere.

[0018] Specifically, the carbonization temperature is 400-1000° C., and the carbonization time is 1-2 hours.

[0019] Specifically, the inert gas is one of nitrogen and argon.

[0020] The present invention also provides a method for removing thallium from water by using a non-metal-doped bulk carbon material, comprising:

[0021] Add non-metallic doped bulk carbon materials into thallium-containing water to directly adsorb and remove thallium;

[0022] Non-metal-doped bulk carbon materials can directly adsorb monovalent and trivalent thallium;

[0023] After the adsorption is completed, the adsorbent is separated and the adsorbent after the reaction is reused.

[0024] Furthermore, the removal rate of thallium by non-metal-doped bulk carbon materials increases with the increase of adsorbent dosage.

[0025] Furthermore, the dosage of the non-metal-doped bulk carbon material is 0.2 to 3.0 g / L.

[0026] Furthermore, the concentration of the thallium-containing water is 10 μg / L to 50 mg / L, and the initial pH of the thallium-containing water is 4 to 13.

[0027] Furthermore, the adsorption temperature is 5 to 35° C., and the adsorption time is 1 to 120 min.

[0028] Furthermore, the adsorbent is separated by filtering or liquid pouring, and the adsorbent after the reaction is desorbed by acid washing and reused.

[0029] Compared with the patent CN114377652A, the thallium removal agent of the present invention is only a single non-metallic doped bulk carbon material, which is green, environmentally friendly, reusable and easy to prepare. The method of removing thallium from water of the present invention has a wider pH range of 4 to 13 for thallium-containing wastewater, and can effectively treat low and high concentration thallium-containing wastewater with a thallium concentration in the range of 10 μg / L to 50 mg / L. After treatment, the thallium concentration in the water body is lower than 5 μg / L, and even reaches the drinking water standard of 0.1 μg / L.

[0030] Compared with the patent CN113526606A, the present invention's thallium removal and adsorption agent is composed of only a single non-metallic doped bulk carbon material, which is green, environmentally friendly, reusable, and easy to prepare. The method of removing thallium from water in the present invention only requires adding an adsorbent. After treatment, the concentration of thallium in the water is less than 5μg / L, and even reaches the drinking water standard of 0.1μg / L.

[0031] Compared with the patent CN113603179A, the present invention is simple to prepare the non-metal doped bulk carbon material adsorbent, which can be obtained by calcination, and can remove thallium in water by directly adding it for adsorption (without adding an oxidant), and has a wider pH range of 4 to 13 for wastewater. After treatment, the concentration of thallium in the water is lower than 5μg / L, and even reaches the drinking water standard of 0.1μg / L.

[0032] The non-metal-doped bulk carbon material of the present invention is simple to prepare, non-toxic and pollution-free, easy to separate and operate, and does not require the addition of any additional reagents. Moreover, under the same adsorbent dosage and thallium concentration conditions, the adsorbent of the present invention is more effective in removing thallium than the above-mentioned disclosed method. The adsorbent of the present invention efficiently removes thallium from water through multiple effects such as chemical adsorption of the lone pair of electrons of non-metal atoms in the adsorbent material coordinated with thallium ions and physical adsorption of the porous structure of the adsorbent material. Non-metal atoms are doped into the carbon skeleton to form covalent bonds with carbon atoms, and the material structure is very stable and can be reused. After the thallium ions coordinate with the lone pair of electrons of the non-metal atoms, they are stably adsorbed on the adsorbent and are not affected by the flow and stirring of the water body and fall off.

[0033] The thallium removal method of the present invention solves the problem of poor thallium removal effect of traditional bulk or nano-carbon materials (such as activated carbon, carbon nanotubes, etc.) from the perspective of thermodynamics and kinetics, and also solves the problems of other thallium removal systems reported in the prior art, such as complex material composition, high cost, poor effect, complex operation, non-reusability, difficulty in separation and secondary pollution. The thallium removal method of the present invention has a wide applicable range for pH value and thallium concentration of thallium-containing wastewater, reusable adsorbent, outstanding effect, greenness, simple operation, and high practical value.

[0034] Compared with the prior art, the technical effects of the present invention are:

[0035] (1) The process conditions are simple, the operation requirements are low, the preparation cost is low, the recovery is easy, no other chemical reagents need to be added, no sludge precipitation is produced, and it can be reused many times.

[0036] (2) Non-metallic doped bulk carbon materials can simultaneously adsorb and remove monovalent thallium and trivalent thallium, and the production and application of the adsorbent is green and pollution-free.

[0037] (3) Non-metallic doped bulk carbon materials can effectively remove thallium from water at pH 4-13 and temperature 5-35°C. The adsorbent can treat thallium-containing water in different environments.

[0038] (4) The removal effect of non-metallic doped bulk carbon materials on thallium-containing wastewater can meet industrial emission standards and even meet my country's drinking water hygiene standards. For example, 1.5g of non-metallic doped bulk carbon materials can treat 331.2L of thallium-containing wastewater with a concentration of 10μg / L at a time and meet industrial emission standards.

[0039] (5) The non-metallic doped bulk carbon material can be acid eluted after absorbing thallium, and the thallium removal effect is not affected after being reused 25 times, which greatly saves costs.

[0040] (6) The excellent qualities of high performance, low cost, no pollution, and easy operation make the thallium removal material and method of the present invention have great practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The nitrogen-doped bulk carbon material prepared in Example 1 has different adsorbent dosages at room temperature for the removal rate of 100 μg / L, pH 7 monovalent thallium-containing water. As the adsorbent dosage increases, the removal rate of thallium in the water is faster and the removal rate is higher. The thallium removal rate of the adsorbent dosage of 0.2g / L to 1.0g / L is above 95% within 3 minutes, and the concentration of residual thallium in the water is ≤5μg / L, meeting the industrial emission standard; when the adsorbent dosage is ≥0.4g / L and the adsorption time is ≥10min, the concentration of residual thallium in the water is ≤0.1μg / L.

[0042] Figure 2 The oxygen-doped bulk carbon material prepared in Example 2 has a removal effect of 0.2 g / L adsorbent on water containing monovalent thallium at different pH values ​​and a concentration of 3 mg / L for 15 minutes at room temperature. In the pH range of 4 to 13, the removal rate of thallium is ≥99.9%, and the concentration of residual thallium in the water is ≤5 μg / L, which meets the industrial emission standard.

[0043] Figure 3 The removal effect of the phosphorus-doped bulk carbon material prepared in Example 3 on the water containing monovalent thallium at pH 7 at different temperatures. Figure 3(a) For water containing 1 mg / L of monovalent thallium, the removal rate of thallium by 1.0 g / L of adsorbent at different temperatures is ≥99.9% in 10 minutes, and it can reach the industrial emission standard in 5 minutes; Figure 3 (b) For water containing monovalent thallium at a high concentration of 5 mg / L, the removal rate of thallium by the adsorbent of 1.0 g / L at different temperatures is above 99.9%, and the industrial emission standard can be reached in 25 minutes.

[0044] Figure 4 The sulfur-doped bulk carbon material prepared in Example 4 removes trivalent thallium at a pH of about 7 and a concentration of 100 μg / L within 60 minutes at room temperature. The removal rate of thallium within 1 minute is above 96%, that is, the industrial emission standard can be reached in 1 minute. It is confirmed that the non-metallic doped bulk carbon material has a high efficiency and rapid removal effect on both monovalent thallium and trivalent thallium.

[0045] Figure 5 The nitrogen-doped bulk carbon material prepared in Example 1 adsorbed thallium at room temperature and then acid eluted, and the removal effect of thallium-containing water of about 100 μg / L pH 7 was observed for 25 consecutive times. The removal rate of thallium was maintained above 95% for 25 consecutive repeated experiments, which could meet the industrial emission standards.

[0046] Figure 6 The column process continuous flow treatment effect of 10μg / L thallium-containing wastewater at room temperature by the oxygen-doped bulk carbon material prepared in Example 2. 1.5g of adsorbent keeps the effluent thallium concentration ≤5μg / L (industrial emission standard), and can treat 331.2L of wastewater. This shows that non-metallic doped bulk carbon materials can treat a large amount of thallium-containing wastewater and have great application prospects.

[0047] Figure 7 The sulfur-doped bulk carbon material prepared in Example 4 has a good removal effect on 50 mg / L monovalent thallium-containing water at pH 7 at room temperature. The removal rate of 3.0 g / L adsorbent on 50 mg / L monovalent thallium water is ≥99.9%, and the concentration of residual thallium in the water after 15 minutes is ≤5 μg / L, which meets the industrial emission standard. It is confirmed that non-metallic doped bulk carbon materials have a good removal effect on low-concentration or high-concentration thallium-containing water.

[0048] Figure 8 The oxygen-doped bulk carbon material prepared in Example 2 is Figure 8 (a) is the zeta potential of oxygen-doped bulk carbon materials. This figure shows that when the pH is lower than 4.13, the removal of thallium is mainly achieved by the chemical adsorption of the lone pair electrons of non-metallic atoms in the material and the coordination of thallium ions. When the pH exceeds 4.13, the removal of thallium is achieved by the multiple effects of physical adsorption and chemical adsorption. Figure 8(b) is the XPS spectrum of the oxygen-doped bulk carbon material before and after the reaction. It can be observed that the peak areas of O=C and H2O decrease after the reaction, and RO - The (Tl-OH and COM) peak areas increased significantly, confirming that the non-metal-doped bulk carbon material of the present invention has chemical adsorption during the adsorption of thallium. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. The described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] Step 1: Cut nitrogen-rich soybeans into block particles, and carbonize them into block carbon materials with a nitrogen doping amount of about 7% at a high temperature of 500° C. in an inert gas atmosphere.

[0052] Step 2: Add different adsorbent doses of 0.2 g / L, 0.4 g / L, 0.6 g / L, 0.8 g / L or 1.0 g / L of nitrogen-doped bulk carbon material to 100 μg / L, pH 7 thallium-containing water at room temperature, conduct a 60-min constant temperature shaking adsorption experiment, and take samples at different time periods.

[0053] Step 3: Filter and separate the nitrogen-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0054] After processing, the results are as follows Figure 1 As shown, it can be seen that with the increase of adsorbent dosage, the removal rate of thallium in water is getting faster and faster. The thallium removal rate of 0.2g / L~1.0g / L adsorbent dosage is above 95% within 3min, and the concentration of residual thallium in water is ≤5μg / L, which meets the industrial emission standard; when the adsorbent dosage is ≥0.4g / L and the adsorption time is ≥10min, the concentration of residual thallium in water is ≤0.1μg / L.

[0055] Example 2

[0056] Step 1: Carbonize the oxygen-rich polyvinyl alcohol block particles at 400° C. in an inert gas atmosphere to form a bulk carbon material with an oxygen doping amount of about 20%.

[0057] Step 2: Add 0.2 g / L oxygen-doped bulk carbon material to 3 mg / L monovalent thallium-containing water at different pH concentrations at room temperature, perform adsorption on a constant temperature shaker for 120 min, and take samples for analysis at different time periods.

[0058] Step 3: Filter and separate the oxygen-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0059] After processing, the results are as follows Figure 2 As shown in the figure, the removal effect of adsorbent dosage 0.2g / L on water containing monovalent thallium at different pH and concentration of 3mg / L for 15min. In the pH range of 4 to 13, the removal rate of thallium is ≥99.9%, and the concentration of residual thallium in the water is ≤5μg / L, which meets the industrial emission standard.

[0060] Example 3

[0061] Step 1: Cut pumpkin seeds rich in phosphorus into block particles, and carbonize them into bulk carbon materials with a phosphorus doping amount of about 5% at a high temperature of 700° C. in an inert gas atmosphere.

[0062] Step 2: Add 1.0 g / L phosphorus-doped bulk carbon material to 1 mg / L, 5 mg / L, pH 7 water containing monovalent thallium, respectively, and perform constant temperature shaking adsorption for 120 min at 5°C, 20°C, and 35°C, respectively, and take samples for analysis at different time periods.

[0063] Step 3: Filter and separate the phosphorus-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0064] After adsorption treatment Figure 3 (a) For water containing 1 mg / L of monovalent thallium, the removal rate of thallium by the adsorbent of 1.0 g / L at different temperatures is above 99.9%, and the industrial emission standard can be reached in 5 minutes; Figure 3 (b) For water containing monovalent thallium at a high concentration of 5 mg / L, the removal rate of thallium by an adsorbent of 1.0 g / L at different temperatures can reach over 99.9%, and the industrial emission standard can be reached in 25 minutes.

[0065] Example 4

[0066] Step 1: Cut the sulfur-rich green onions into appropriate sizes, and then carbonize them into bulk carbon materials with a sulfur doping content of about 15% at 600° C. in an inert gas atmosphere.

[0067] Step 2: Add 0.6 g / L sulfur-doped bulk carbon material to a trivalent thallium aqueous solution with a concentration of 100 μg / L and pH 7 at room temperature, perform adsorption on a constant temperature shaker for 60 minutes, and perform sampling and analysis at different time periods.

[0068] Step 3: Filter and separate the sulfur-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0069] The removal results of trivalent thallium after adsorption treatment are as follows: Figure 4 As shown, the removal rate of thallium is above 96% within 1 minute, that is, the industrial emission standard can be reached in 1 minute. It is confirmed that non-metallic doped bulk carbon materials also have a high efficiency and rapid removal effect on trivalent thallium.

[0070] Example 5

[0071] Step 1: Add 0.4 g / L of the nitrogen-doped bulk carbon material prepared in Example 1 to 100 μg / L of monovalent thallium-containing water at pH 7 at room temperature, and perform shaking table adsorption for 120 min.

[0072] Step 2: Filter and separate the nitrogen-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0073] Step 3: After the separated nitrogen-doped bulk carbon material is desorbed with dilute hydrochloric acid, the material is washed to neutrality and then added to a monovalent thallium-containing water body with a concentration of 100 μg / L and a pH of about 7, and then adsorbed on a shaking table for 120 minutes, and the water body is sampled and analyzed.

[0074] Step 4: Repeat steps 1 to 3 to perform multiple adsorption-desorption experiments.

[0075] After processing, the results are as follows Figure 5 As shown, in 25 consecutive adsorption-desorption experiments, the removal rate of thallium was above 95% each time, and the wastewater reached the industrial discharge standard.

[0076] Example 6

[0077] Step 1: Fill 0.2 g / L of the oxygen-doped bulk carbon material prepared in Example 2 into a polyethylene column with an effective length of 12.9 cm and a diameter of 1.6 cm.

[0078] Step 2: 10 μg / L monovalent thallium wastewater is injected into the polyethylene column using a peristaltic pump at a flow rate of 2 mL / min, and the empty bed contact time (EBCT) is about 12.96 min.

[0079] Step 3: Take samples of the treated effluent at regular intervals.

[0080] Step 4: Use an inductively coupled plasma mass spectrometer to measure the concentration of thallium in the water.

[0081] After processing, the results are as follows Figure 6As shown, the thallium concentration of the effluent is ≤0.1 μg / L, and the treated water volume is 10109.6 BV (262.08 L); the thallium concentration of the effluent is ≤5 μg / L, and the treated water volume is 12775.9 BV (331.2 L). The powerful continuous flow processing capacity shows that the non-metal-doped bulk carbon material of the present invention has a good practical application prospect.

[0082] Example 7

[0083] Step 1: Add 3.0 g / L of the sulfur-doped bulk carbon material prepared in Example 4 to 50 mg / L of monovalent thallium-containing water at pH 7 at room temperature and perform shaking table adsorption for 60 min.

[0084] Step 2: Filter and separate the sulfur-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0085] Step 3: Filter and separate the sulfur-doped bulk carbon material from the thallium-containing water body, and measure the thallium concentration in the water body using an inductively coupled plasma mass spectrometer.

[0086] After processing, the results are as follows Figure 7 As shown, the removal rate of 3.0g / L adsorbent for 50mg / L monovalent thallium water is above 99.9%, and the concentration of residual thallium in the water after 15min is ≤5μg / L, which meets the industrial emission standard. This shows that the non-metallic doped bulk carbon material of the present invention also has a good removal effect on high-concentration thallium-containing water.

[0087] Example 8

[0088] Step 1: Carbonize the polyacrylamide block particles rich in oxygen and nitrogen into a block carbon material with oxygen and nitrogen doping amounts of about 15% and 12% at 450° C. under the protection of an inert gas atmosphere.

[0089] Step 2: Add 0.4 g / L nitrogen-doped bulk carbon material into 2 mg / L neutral thallium-containing water at room temperature, conduct a 120-min constant temperature shaker adsorption experiment, and take samples at different time periods.

[0090] Step 3: solid-liquid separation: the nitrogen-doped bulk carbon material is taken out from the thallium-containing water body, and the thallium in the water body is adsorbed on the bulk carbon material.

[0091] Step 4: Use an inductively coupled plasma mass spectrometer to measure the concentration of thallium in the water.

[0092] After treatment, the thallium removal rate of 0.4g / L adsorbent is above 99.8% within 7 minutes, that is, it can meet the industrial emission standards in 7 minutes.

[0093] Example 9

[0094] Step 1: Carbonize the polyphosphazene block particles rich in phosphorus and nitrogen into a bulk carbon material with phosphorus and nitrogen doping amounts of about 4% and 7% at a high temperature of 800° C. under the protection of an inert gas atmosphere.

[0095] Step 2: Add 0.2 g / L oxygen-doped bulk carbon material into 500 μg / L neutral thallium-containing water at room temperature, conduct a 120-min constant temperature shaker adsorption experiment, and take samples at different time periods.

[0096] Step 3: solid-liquid separation: the nitrogen-doped bulk carbon material is taken out from the thallium-containing water body, and the thallium in the water body is adsorbed on the bulk carbon material.

[0097] Step 4: Use an inductively coupled plasma mass spectrometer to measure the concentration of thallium in the water.

[0098] After treatment, the thallium concentration in the solution was lower than 5 μg / L after 10 minutes of adsorption by 0.2 g / L adsorbent, which means that the industrial emission standard can be met in 10 minutes.

[0099] Comparative Example 1

[0100] Step 1: Add 1 g / L adsorbent powdered activated carbon (particle size 5-8 μm) to 100 μg / L monovalent thallium-containing water at pH 7 at room temperature, perform adsorption on a constant temperature shaker for 120 minutes, and take samples for analysis at different time periods.

[0101] Step 2: After standing, the powdered activated carbon is filtered and separated from the thallium-containing water, and the concentration of thallium in the water is measured using an inductively coupled plasma mass spectrometer.

[0102] After adsorption treatment, the thallium concentration in the solution was 13.46 μg / L after 120 minutes of adsorption by 1 g / L powdered activated carbon adsorbent, and the thallium removal effect was far worse than that of the above implementation example.

[0103] Comparative Example 2

[0104] Step 1: Add 1 g / L adsorbent amount of carbon nanotube powder to 100 μg / L monovalent thallium-containing water at pH 7 at room temperature, perform adsorption on a constant temperature shaker for 120 minutes, and take samples for analysis at different time periods.

[0105] Step 2: After standing, filter and separate the carbon nanotube powder from the thallium-containing water, and measure the thallium concentration in the water using an inductively coupled plasma mass spectrometer.

[0106] After adsorption treatment, the thallium concentration in the solution was 79.26 μg / L after 120 minutes of adsorption by 1 g / L carbon nanotube powder adsorbent, and the thallium removal effect was far worse than that of the above implementation examples.

[0107] The method for removing thallium from water of the present invention is simple to operate. Non-metallic doped bulk carbon material is directly added to the thallium-containing water body. The adsorbent can adsorb monovalent thallium and trivalent thallium at the same time without adding any additional reagents. The adsorbent of the present invention only needs 0.2g / L of adsorbent for thallium-containing water bodies of ≤100μg / L, and can reach industrial emission standards within 3 minutes. The adsorbent of 0.4g / L to 1.0g / L can achieve a thallium removal rate of more than 99.9%; high-concentration (50mg / L) thallium-containing water bodies can also be treated to industrial emission standards. The adsorbent can quickly and efficiently treat thallium-containing water bodies at different temperatures and pH values ​​between 4 and 13 to industrial emission standards. The excellent qualities of high performance, low cost, pollution-free, and easy operation make the thallium removal material and method of the present invention have great practical application value.

Claims

1. A method for removing thallium from water using non-metal-doped bulk carbon materials, characterized in that: include: Adding non-metal-doped bulk carbon material into a thallium-containing water body; Non-metal-doped bulk carbon materials are used to adsorb trivalent thallium; After the adsorption is completed, the adsorbent is separated and the adsorbent after the reaction is reused; The non-metal-doped bulk carbon material is obtained by directly carbonizing a bulk precursor rich in non-metal elements; the non-metal elements are one or more of N, O, P and S; The doping amount of the non-metal is 5% to 35%; The non-metal-doped bulk carbon material has a porous structure; The block precursor rich in non-metallic elements is a synthetic polymer material; The synthetic polymer material is one of polyvinyl alcohol, polyoxymethylene, polylactic acid, polyacrylic acid, polyacrylic acid derivatives, polythiophene, polyamide, polypyrrole, polyphosphazene, polyurethane, polyether, polyester, polyphenylene sulfide, and polyurea.

2. The method for removing thallium from water using non-metal-doped bulk carbon materials according to claim 1, characterized in that: The preparation process of non-metal-doped bulk carbon materials is as follows: The non-metal-rich bulk precursor is carbonized into a non-metal-doped bulk carbon material using high temperature in an inert gas atmosphere.

3. The method for removing thallium from water by using non-metal-doped bulk carbon materials according to claim 2, characterized in that: The carbonization temperature is 400-1000° C., and the carbonization time is 1-2 hours.

4. The method for removing thallium from water by using non-metal-doped bulk carbon materials according to claim 1, characterized in that: The dosage of the non-metal doped bulk carbon material is 0.2-3.0 g / L.

5. The method for removing thallium from water by using non-metal-doped bulk carbon materials according to claim 4, characterized in that: The concentration of thallium-containing water is 10 μg / L to 50 mg / L, the initial pH of the thallium-containing water is 4 to 13, the adsorption temperature is 5 to 35° C., and the adsorption time is 1 to 120 min.

Citation Information

Patent Citations

  • Thallium removal agent and preparation method thereof

    CN113526606A

  • Preparation of composite biochar and method for removing thallium-containing ammonia nitrogen wastewater by using composite biochar

    CN113603179A

  • Nano-composite thallium removal agent and method for treating thallium-containing wastewater by using nano-composite thallium removal agent

    CN114377652A

  • Preparation method of watermelon peel biochar and application of watermelon peel biochar in removal of thallium in wastewater

    CN108435135A